"Sampling with a Rope-used to Estimate, along with Basal Area, other Characters Like Volume Etc." - Satyamurthi, K. R. (Indian Forester, 1980)
The sampling with a rope method can be used to estimate apart from basal area other characters like volume which are related with the tree's trunk. The procedure for this is described. Equation (4) gives the basic equation.